FROM CASH TRANSFERS TO AMAL SHALIH: THE ROLE OF ISLAMIC FINANCIAL LITERACY IN HUMAN CAPITAL DEVELOPMENT - Asep Asep; Dedy Sukmana; Rani Suryani; Syafuddin Syafuddin; Nurul Aisyah (Universitas Nurul Jadid, 2026)
This study examines the role of Islamic financial literacy (IFL) in mediating the relationship between conditional cash transfers and human capital development among beneficiaries of Indonesia’s Program Keluarga Harapan (PKH). Using a quantitative cross-sectional design and data from 420 households across three provinces, the study applies Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed model. The findings reveal that while cash transfers have a positive but limited direct effect on human capital development, Islamic financial literacy exerts a stronger and more significant influence. Importantly, IFL mediates more than half of the total effect of cash transfers, transforming financial assistance into productive investments in education, healthcare, and economic resilience. Furthermore, IFL facilitates the conversion of financial resources into amal shalih, reflected in ethical financial behavior such as zakat participation, avoidance of riba-based debt, and socially oriented economic practices. This study contributes to the literature by integrating Islamic ethical dimensions into human capital theory and operationalizing amal shalih as a measurable economic outcome. The findings suggest that poverty alleviation programs should incorporate value-based financial education to enhance both economic and moral development outcomes.